Elucidation of an essential function of the unique charged domain of Plasmodium topoisomerase III. Issue 24 (24th December 2020) - Bansod, Shephali; Bung, Navneet; Singh, Priyanka; Suthram, Niranjan; Choudhury, Himashree; Roy, Arijit; Bulusu, Gopalakrishnan; Bhattacharyya, Sunanda
Abstract : Topoisomerase III (TopoIII) along with RecQ helicases are required for the resolution of abnormal DNA structures that result from the stalling of replication forks. Sequence analyses have identified a putative TopoIII in the Plasmodium falciparum genome (PfTopoIII). PfTopoIII shows dual nuclear and mitochondrial localization. The expression and association of PfTopoIII with mtDNA are tightly linked to the asexual replication of the parasite. In this study, we observed that PfTopoIII physically interacts with PfBlm and PfWrn. Sequence alignment and domain analyses have revealed that it contains a unique positively charged region, spanning 85 amino acids, within domain II. A molecular dynamics simulation study revealed that this unstructured domain communicates with DNA and attains a thermodynamically stable state upon DNA binding. Here, we found that the association between PfTopoIII and the mitochondrial genome is negatively affected by the absence of the charged domain. Our study shows that PfTOPOIII can completely rescue the slow growth phenotype of the ΔtopoIII strain in Saccharomyces cerevisiae, but neither PfY421FtopoIII (catalytic-active site mutant) nor Pf(Δ259–337)topoIII (charged region deletion mutant) can functionally complement ScTOPOIII . Hydroxyurea (HU) led to stalling of the replication fork during the S phase, caused moderate toxicity to the growth of P. falciparum, and was associated with concomitant transcriptional up-regulation of PfTOPOIII . In addition, ectopic expression of PfTOPOIII reversed HU-induced toxicity. Interestingly, the expression of Pf ( Δ259–337 ) topoIII failed to reverse HU-mediated toxicity. Taken together, our results establish the importance of TopoIII during Plasmodium replication and emphasize the essential requirement of the charged domain in PfTopoIII function.